Effect of PCB as partial replacement of fine aggregate and coarse aggregate in concrete. (2022) - Pothinathan, S.K.M.; Kumar, Pream; Arunachelam, N.; Gnanaraj, S. Christopher
Abstract: Concrete, being a universal building material it is used as a medium to dispose of industrial by-products and waste materials in it. This may improves certain characteristics when its used as filler material or binder. This action also reduce the harmful environmental hazards by dumping those materials directly onto the earth. In this study, electronic wastes – Printed Circuit Boards (PCB) was used as replacement to aggregate. This PCB was expelled out from the hardware industry and used in study for development of e-concrete. Owing to its lower recycling rate, it steadily becomes perilous to the environment thus paving way for an ecological imbalance. The utilization of PCB as aggregates in concrete may also mitigate the cost of construction by minimizing the usage of the aggregates procured from nature thus inducing greener concrete. This experimental study is an attempt to introduce the PCB as a partial substitute for both the fine aggregate and coarse aggregate at different percentages of 0%, 5%, 10%, 15% and 20%. The e-concrete thus developed and compared with conventional concrete for its mechanical properties and long-term behaviour against sulfate attack. The results indicate that replacing both the fine aggregate and coarse aggregate at 5% tend to improve the concrete behaviour adequately enabling the PCB as an ideal choice of replacement thus providing a safer choice to eliminate this e-waste without affecting the ecological balance.